2012
DOI: 10.1096/fj.11-199984
|View full text |Cite
|
Sign up to set email alerts
|

New experimental data linking secondhand smoke exposure to lung cancer in nonsmokers

Abstract: Secondhand smoke (SHS) exposure is a known risk factor for lung cancer development in lifelong nonsmokers; however, the mechanistic involvement of SHS in the genesis of this malignancy remains elusive. The present study is the first comprehensive investigation of SHS mutagenicity in vivo, in which we have established the mutagenic effects of SHS in transgenic Big Blue mice, and subsequently found correlations between our experimental findings and those obtained from our analysis of the largest database of muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 34 publications
10
26
0
Order By: Relevance
“…7 E, F and 8 C ). The above‐specified mutational signatures of these 3 carcinogens are comparable to those found previously in the same model system using the conventional low‐throughput method (62, 70, 71).…”
Section: Development Of a High‐throughput Next‐generation Sequencing‐supporting
confidence: 81%
“…7 E, F and 8 C ). The above‐specified mutational signatures of these 3 carcinogens are comparable to those found previously in the same model system using the conventional low‐throughput method (62, 70, 71).…”
Section: Development Of a High‐throughput Next‐generation Sequencing‐supporting
confidence: 81%
“…In vivo treatment of Big Blue® mice with 4-ABP, a known bladder carcinogen with moderate mutagenic potency (13), resulted in a 9.9-fold increase in background cII mutant frequency from 2.09 ± 0.20 × 10 − 5 in bladder DNA of control (solvent-treated) mice to 20.62 ± 4.77 × 10 − 5 in bladder DNA of 4-ABP-treated mice ( P  = 0.0079). In vivo exposure of Big Blue® mice to SHS, a known pulmonary carcinogen with comparatively weak mutagenic potency (12), resulted in a 2.1-fold increase in background cII mutant frequency from 2.00 ± 0.29 × 10 − 5 in lung DNA of control (clean-air-treated) mice to 4.09 ± 0.79 × 10 − 5 in lung DNA of SHS-treated mice ( P  = 0.0011).…”
Section: Resultsmentioning
confidence: 99%
“…However, the mutation detection systems employed in these studies may not necessarily represent some of the key determinants of mutagenesis in mammalian cells, for example, chromatin structure, DNA sequence contexts, fidelity and efficiency of DNA polymerases and DNA repair (4,35–38). In addition, these systems are not suitable for investigating organ-specific mutagenicity in relation to tumorigenesis, which is a unique property of certain carcinogens (12,13). The latter is reflective of the need for studying target-organ mutagenesis in animal models of tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation spectrum analysis has shown that the rate of G to T transversions in the lung cancer of smokers (about 30%) is higher than that of non-smokers (10%–15%) [90, 91, 95]. However, experimental inhalation of environmental tobacco smoke to Big Blue mice showed that the most common mutation induced on the cII gene was G to A transition and the next was G to T transversion [96]. …”
Section: Introductionmentioning
confidence: 99%